Conductive particles, method for producing conductive particles, conductive material, and connection structure
Patent Information
- Application Number
- JP2022019796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-03-03
- Filing Date
- 2022-02-10
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2036-03-02
AI Technical Summary
【0028】 本発明に係る導電性粒子では、基材粒子の表面上に導電部が配置されており、上記導電部が水素原子を含まないか、又は、上記導電部が水素原子を80μg/g以下で含むので、導電部に割れを生じ難くすることができ、耐酸性を高めることができ、従って接続信頼性を高めることができる。
Smart Images

Figure 0007652725000002 
Figure 0007652725000003 
Figure 0007652725000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive particle having a conductive portion disposed on the surface of a base particle, and a method for producing the conductive particle. The present invention also relates to a conductive material and a connection structure using the conductive particle. [Background technology]
[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known, and in such anisotropic conductive materials, a plurality of conductive particles are dispersed in a binder resin.
[0003] The anisotropic conductive materials are used to obtain various connection structures, for example, connecting a flexible printed circuit board to a glass substrate (FOG (Film on Glass)), connecting a semiconductor chip to a flexible printed circuit board (COF (Chip on Film)), connecting a semiconductor chip to a glass substrate (COG (Chip on Glass)), and connecting a flexible printed circuit board to a glass epoxy substrate (FOB (Film on Board)).
[0004] As an example of the conductive particles, the following Patent Document 1 discloses conductive particles having a base particle and a conductive metal layer covering the surface of the base particle. The conductive metal layer includes a nickel layer. In the conductive particles, the crystallite size of nickel in the
[0111] direction measured by powder X-ray analysis is 3 nm or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2013 / 042785A1 Summary of the Invention [Problem to be solved by the invention]
[0006] When an anisotropic conductive material is used to electrically connect, for example, an electrode of a semiconductor chip and an electrode of a glass substrate, an anisotropic conductive material containing conductive particles is disposed on the glass substrate. Next, the semiconductor chips are stacked, and heated and pressurized. This causes the anisotropic conductive material to harden, electrically connecting the electrodes via the conductive particles to obtain a connection structure. An example of a connection structure obtained by such a method is a liquid crystal display element.
[0007] In the liquid crystal display element, the frame of the liquid crystal panel is narrowed and the glass substrate is thinned. This causes distortion in the mounting portion, which makes it easy for display unevenness to occur. In order to suppress the display unevenness, it is required to perform compression bonding at a low temperature.
[0008] However, when the pressure is applied at a low temperature, the melt viscosity of the anisotropic conductive material becomes high. Therefore, when the pressure is applied at a low temperature, in order to prevent voids from being generated, it is necessary to increase the pressure. As a result, a large stress is applied to the conductive particles. In addition, in manufacturing methods other than the above-mentioned manufacturing method of the connection structure, and even before the conductive particles are used, a large stress may be applied to the conductive particles.
[0009] In conventional conductive particles such as those described in Patent Document 1, cracks may occur in the conductive layer when stress is applied to the conductive particles. As a result, when electrodes are connected to obtain a connection structure, the initial connection resistance may increase and the electrical conductivity reliability may decrease.
[0010] Furthermore, when a connection structure in which a conductive connection is made using conventional conductive particles is exposed to the presence of an acid, the connection resistance between the electrodes may increase.
[0011] Furthermore, when conventional conductive particles such as those described in Patent Document 1 are exposed to the presence of acid, corrosion of the conductive layer may occur. Also, when a connection structure is obtained by connecting electrodes using conventional conductive particles, the connection resistance between the electrodes may increase when the connection structure is exposed to the presence of acid.
[0012] An object of the present invention is to provide conductive particles and a method for manufacturing conductive particles that can make the conductive part less susceptible to cracking, improve acid resistance, and therefore improve connection reliability.
[0013] Another object of the present invention is to provide a conductive material and a connection structure using the conductive particles. [Means for solving the problem]
[0014] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle and a conductive portion disposed on a surface of the base particle, the conductive portion not containing hydrogen atoms or the conductive portion containing hydrogen atoms in an amount of 80 μg / g or less.
[0015] In a specific aspect of the conductive particle according to the present invention, the conductive portion includes a conductive portion having a crystalline structure, and upon cross-sectional observation of the conductive portion having the crystalline structure, the crystallite size in the conductive portion having the crystalline structure is 50 nm or more.
[0016] In a specific aspect of the conductive particle according to the present invention, the conductive portion includes a conductive portion having a crystalline structure, and in the conductive portion having a crystalline structure, a crystallite size calculated as an average value of the crystallite sizes of the (111) plane, the (200) plane, the (220) plane, the (311) plane and the (222) plane, calculated from the half-width of a diffraction peak obtained by X-ray diffraction and the Scherrer equation, is 50 nm or more.
[0017] In a specific aspect of the conductive particle according to the present invention, the conductive portion includes a conductive portion having a crystalline structure, and in the conductive portion having a crystalline structure, the crystallite size calculated from the half-width of a diffraction peak obtained by X-ray diffraction and the Williamson-Hall equation is 50 nm or more.
[0018] In a specific aspect of the conductive particles according to the present invention, the compressive modulus when compressed by 10% is 3000 N / mm 2 That's all.
[0019] In a specific aspect of the conductive particle according to the present invention, the conductive portion has a Vickers hardness of 200 or more.
[0020] In a specific aspect of the conductive particle according to the present invention, the conductive portion contains at least nickel, palladium, ruthenium, copper, tungsten, molybdenum, phosphorus, boron, gold, platinum, or tin.
[0021] In a specific aspect of the conductive particle according to the present invention, the conductive portion contains at least nickel.
[0022] In a specific aspect of the conductive particle according to the present invention, the base particle is a resin particle or an organic-inorganic hybrid particle.
[0023] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a plurality of protrusions on an outer surface of the conductive portion.
[0024] In a specific aspect of the conductive particle according to the present invention, the conductive particle includes an insulating material disposed on an outer surface of the conductive portion.
[0025] According to a broad aspect of the present invention, there is provided a method for producing the above-mentioned conductive particles, which comprises a step of annealing a conductive particle having a base particle and a conductive portion arranged on the surface of the base particle at 200°C or higher, and by the annealing treatment, a conductive particle is obtained in which the conductive portion does not contain hydrogen atoms or the conductive portion contains hydrogen atoms at 80 μg / g or less.
[0026] According to a broad aspect of the present invention, there is provided a conductive material including the above-described conductive particles and a binder resin.
[0027] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member, a second connection target member, and a connection portion connecting the first connection target member and the second connection target member, wherein the material of the connection portion is the conductive particles described above, or a conductive material containing the conductive particles and a binder resin. Effect of the Invention
[0028] In the conductive particle of the present invention, a conductive portion is disposed on the surface of a base particle, and the conductive portion does not contain hydrogen atoms or contains hydrogen atoms at 80 μg / g or less, so that the conductive portion is less susceptible to cracking, acid resistance can be increased, and connection reliability can be improved. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a front cross-sectional view that typically shows a connection structure using conductive particles according to the first embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The present invention will be described in detail below.
[0031] (Conductive particles) The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle.
[0032] In the conductive particle according to the present invention, the conductive portion does not contain hydrogen atoms or contains hydrogen atoms in an amount of 80 μg / g or less, i.e., the conductive particle according to the present invention has an extremely low content of hydrogen atoms in the conductive portion.
[0033] Since the present invention has the above-mentioned configuration, it is possible to make the conductive portion less susceptible to cracking, to improve acid resistance, and therefore to improve connection reliability.
[0034] In addition, by making the conductive portion less susceptible to cracking, it is possible to obtain a connection structure having sufficiently low connection resistance between electrodes and excellent electrical reliability, even if the conductive material is hardened at a relatively low temperature and compression bonding is performed in a state in which the melt viscosity of the conductive material is high. By using the conductive particles according to the present invention, it is possible to accommodate narrower frame widths and thinner thicknesses of connection target components.
[0035] Furthermore, in the present invention, since cracks are less likely to occur in the conductive portion, the connection resistance can be maintained low even when a connection structure is obtained using conductive particles exposed to the presence of acid, or when the connection structure is exposed to the presence of acid.
[0036] From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, the lower the hydrogen atom content in the conductive part, the better. The hydrogen atom content in the conductive part is preferably 60 μg / g or less, more preferably 40 μg / g or less, and most preferably 0 μg / g (not contained).
[0037] Methods for measuring the content of hydrogen atoms in the conductive portion include a temperature programmed desorption method, a high-temperature dissolved hydrogen extraction method, a glycerin substitution method, an electrochemical release method, etc. The temperature programmed desorption method is preferred, and the temperature programmed desorption method using a temperature programmed desorption hydrogen analyzer is more preferred.
[0038] The content of hydrogen atoms in the conductive portion can be measured as follows.
[0039] In the thermal desorption method using a thermal desorption hydrogen analyzer, the conductive part is heated in the thermal desorption device, and the trace amounts of hydrogen that are generated are measured by a sensor gas chromatograph. Under a constant pressure of 3 GPa, the evacuated conductive part is gradually heated from 50°C to 400°C at a rate of 5°C / min. The released hydrogen atoms are measured by a sensor gas chromatograph.
[0040] Regarding the method of calculating the hydrogen atom content in the conductive part, first, the hydrogen atom content in the conductive particle is measured to obtain a measured value of the hydrogen atom content. Next, the hydrogen atom content in the base particle before forming the conductive part is measured to obtain a measured value of the hydrogen atom content. The measured hydrogen atom content in the base particle is subtracted from the measured hydrogen atom content in the conductive particle to obtain a value of the hydrogen atom content in the conductive part.
[0041] Hydrogen atom content in conductive part = hydrogen atom content in conductive particle - hydrogen atom content in base particle
[0042] In addition, the method for calculating the hydrogen atom content in the conductive part can be obtained by peeling the conductive part from the conductive particle, collecting only the conductive part, and measuring the hydrogen atom content in the conductive part to obtain a measured value of the hydrogen atom content. The method for collecting a sample of the conductive part to be measured is to first crush the conductive particle using a ball mill with zirconia balls, and completely peel the conductive part from the base particle to obtain a sample. The sample is separated into the conductive part and the base particle using a dry sieve, and only the conductive part is collected.
[0043] Generally, the conductive part of a conductive particle contains a relatively large number of hydrogen atoms. For example, when the conductive part is formed by electroless plating, the conductive particle has a large plating surface area, so a high concentration of reducing agent is required. As a result, hydrogen is generated by the oxidative decomposition of a large amount of reducing agent, so the conductive part contains a relatively large number of hydrogen atoms. In the present invention, the hydrogen atoms in the conductive part are actively reduced.
[0044] Methods for reducing the content of hydrogen atoms in the conductive part include annealing after forming the conductive part, reducing the concentration of the reducing agent used during plating, adding a surfactant during plating to reduce the surface tension of the base particle surface and increase hydrogen desorption, increasing the stirring speed of the plating solution during plating to increase hydrogen desorption, and controlling the reaction temperature and pH during plating to suppress the self-decomposition reaction of the reducing agent, etc. These methods can be used in combination so that the content of hydrogen atoms is sufficiently reduced.
[0045] From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, the crystallite size in the conductive part is preferably 50 nm or more, more preferably 100 nm or more. From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, it is preferable that the conductive part includes a conductive part having a crystalline structure. From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, the crystallite size in the conductive part having the crystalline structure is preferably 50 nm or more, more preferably 100 nm or more.
[0046] From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, in the conductive part having the above crystal structure, the crystallite size calculated from the half-width of the diffraction peak obtained by X-ray diffraction and the Williamson-Hall equation is preferably 50 nm or more, more preferably 100 nm or more.
[0047] From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, in the conductive part having the above crystal structure, the crystallite size calculated as the average value of the crystallite sizes of the (111), (200), (220), (311) and (222) planes calculated from the half-width of the diffraction peak obtained by X-ray diffraction and the Scherrer equation is preferably 50 nm or more, more preferably 100 nm or more.
[0048] The crystallite size can be measured as follows.
[0049] The obtained conductive particles are added to Kulzer's "Technovit 4000" so that the content is 30% by weight, and dispersed to prepare a conductive particle inspection embedding resin. A cross section of the conductive particle is cut out using an ion milling device (Hitachi High-Technologies' "IM4000") so as to pass through the center of the dispersed conductive particles in the inspection embedding resin.
[0050] Using FE-SEM-EBSP, crystal grain mapping measurement is performed on the cross section of the conductive part having a crystalline structure in the conductive particle. The crystallite size is determined by checking the particle size distribution chart of the crystallite size.
[0051] The crystallite size can be measured as follows.
[0052] Powder X-ray diffraction measurements are performed using an X-ray diffractometer (Rigaku Denki Co., Ltd., "RINT2500VHF"). The crystallite size is determined from the half-width of the diffraction peak obtained by X-ray diffraction using CuKα radiation and the average crystallite size of the (111), (200), (220), (311), and (222) planes calculated from the Scherrer equation.
[0053] The conductive particle is preferably a conductive particle comprising a base particle and a conductive portion, the conductive portion including a first conductive portion having a crystalline structure and a second conductive portion having a crystalline structure, the first conductive portion being disposed on the surface of the base particle, and the second conductive portion being disposed on the outer surface of the first conductive portion so as to contact the first conductive portion. The crystallite size of the first conductive portion in the conductive particle may be measured.
[0054] The conductive particle includes a base particle and a conductive portion, and the conductive portion is preferably only a first conductive portion having a crystalline structure, and the first conductive portion is disposed on the surface of the base particle. The crystallite size of the first conductive portion of the conductive particle may be measured.
[0055] The crystallite size can be calculated by the following Scherrer formula.
[0056] D=kλ / βcosθ D: Crystallite size K: Scherrer constant λ: wavelength of X-rays β: Half-width [rad] θ: Diffraction angle
[0057] The crystallite size can be calculated by the Williamson-Hall equation below.
[0058] Δ2θ·cosθ / λ=0.9 / D+2ε·sinθ / λ D: Crystallite size λ: wavelength of X-rays Δ2θ: Half-width [rad] θ: Diffraction angle ε: Lattice strain
[0059] The crystallite size is determined by plotting 2sinθ / λ on the horizontal axis and Δ2θ·cosθ / λ on the vertical axis according to the Williamson-Hall equation, and calculating the crystallite size from the intercept of the straight line on the plot.
[0060] From the viewpoint of further suppressing cracking of the conductive portion and further enhancing the acid resistance, the compressive elastic modulus (10% K value) when the conductive particles are compressed by 10% is preferably 3000 N / mm 2 More preferably, 5000N / mm 2 or more, preferably 20000N / mm 2 Less than or equal to 10,000 N / mm 2 The following is the result.
[0061] The 10% K value of the conductive particles can be measured as follows.
[0062] Using a micro-compression tester, the conductive particles are compressed with a smooth cylindrical indenter end face (diameter 50 μm, made of diamond) under conditions of 25° C. and a maximum test load of 90 mN for 30 seconds. The load value (N) and compression displacement (mm) at this time are measured. From the obtained measured values, the compression modulus can be calculated by the following formula. As the micro-compression tester, for example, Fischer Scope H-100 manufactured by Fischer Co., Ltd. can be used.
[0063] K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2 F: Load value (N) when the conductive particles are compressed by 10% S: Compressive displacement (mm) when the conductive particles are compressed and deformed by 10% R: Radius of conductive particle (mm)
[0064] From the viewpoint of further suppressing cracking of the conductive portion and further enhancing acid resistance, the Vickers hardness of the conductive portion in the conductive particle is preferably 200 or more, more preferably 300 or more, even more preferably 500 or more, and preferably 1000 or less, more preferably 800 or less. From the viewpoint of further suppressing cracking of the conductive portion and further enhancing acid resistance, the Vickers hardness of the conductive portion having the crystal structure in the conductive particle is preferably 200 or more, more preferably 300 or more, even more preferably 500 or more, and preferably 1000 or less, more preferably 800 or less.
[0065] From the viewpoint of further reducing the connection resistance and further increasing the conduction reliability, it is preferable that the conductive particles have a plurality of protrusions on the outer surface of the conductive part. Furthermore, it is preferable that the conductive particles have a plurality of core substances that raise the outer surface of the conductive part so as to form a plurality of the protrusions in the conductive part.
[0066] From the viewpoint of further lowering the connection resistance and further increasing the conductivity reliability, the surface area of the portion having the protrusions is preferably 10% or more, more preferably 30% or more, and is preferably 95% or less, more preferably 90% or less, of the total surface area (100%) of the conductive particle.
[0067] The surface area of the protrusions is determined by observing the conductive particles with an electron microscope or optical microscope and calculating the percentage of the surface area of the protrusions relative to the projected area of the particle. In the case of multiple conductive particles, the surface area of the protrusions is determined by observing 10 arbitrary conductive particles with an electron microscope or field emission scanning electron microscope (FE-SEM) and calculating the average percentage of the surface area of the protrusions relative to the projected area of the particle.
[0068] The present invention will now be described in detail with reference to the drawings.
[0069] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.
[0070] The conductive particle 1 shown in Fig. 1 has a base particle 2 and a conductive portion 3. The conductive portion 3 is disposed on the surface of the base particle 2. The conductive portion 3 is in contact with the surface of the base particle 2. The conductive particle 1 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 3. In the conductive particle 1, the conductive portion 3 is a single-layer conductive portion (conductive layer).
[0071] The conductive particle 1 does not have a core substance, unlike the conductive particles 11 and 21 described below. The conductive particle 1 does not have protrusions on its conductive surface, and does not have protrusions on the outer surface of the conductive part 3. The conductive particle 1 is spherical.
[0072] Thus, the conductive particles according to the present invention may not have protrusions on the conductive surface, may not have protrusions on the outer surface of the conductive part, and may be spherical. Also, the conductive particle 1 does not have an insulating material, unlike the conductive particles 11 and 21 described later. However, the conductive particle 1 may have an insulating material arranged on the outer surface of the conductive part 3.
[0073] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.
[0074] 2 has a base particle 2, a conductive portion 12, a plurality of core materials 13, and a plurality of insulating materials 14. The conductive portion 12 is disposed on the surface of the base particle 2 so as to be in contact with the base particle 2. In the conductive particle 11, the conductive portion 12 is a single-layer conductive portion (conductive layer).
[0075] The conductive particle 11 has a plurality of protrusions 11a on its conductive surface. The conductive portion 12 has a plurality of protrusions 12a on its outer surface. A plurality of core substances 13 are disposed on the surface of the base particle 2. The plurality of core substances 13 are embedded in the conductive portion 12. The core substances 13 are disposed inside the protrusions 11a, 12a. The conductive portion 12 covers the plurality of core substances 13. The outer surface of the conductive portion 12 is raised by the plurality of core substances 13, forming the protrusions 11a, 12a.
[0076] The conductive particle 11 has an insulating material 14 disposed on the outer surface of the conductive portion 12. At least a portion of the outer surface of the conductive portion 12 is covered with the insulating material 14. The insulating material 14 is formed of a material having insulating properties, and is an insulating particle. In this way, the conductive particle according to the present invention may have an insulating material disposed on the outer surface of the conductive portion. However, the conductive particle according to the present invention does not necessarily have to have an insulating material.
[0077] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.
[0078] 3 has a base particle 2, a conductive portion 22, a plurality of core materials 13, and a plurality of insulating materials 14. The conductive portion 22 as a whole has a first conductive portion 22A on the base particle 2 side, and a second conductive portion 22B on the side opposite to the base particle 2 side.
[0079] The only difference between conductive particle 11 and conductive particle 21 is the conductive portion. That is, conductive particle 11 has conductive portion 12 with a single layer structure, whereas conductive particle 21 has first conductive portion 22A and second conductive portion 22B with a two-layer structure. First conductive portion 22A and second conductive portion 22B are formed as separate conductive portions.
[0080] The first conductive portion 22A is disposed on the surface of the base particle 2. The first conductive portion 22A is disposed between the base particle 2 and the second conductive portion 22B. The first conductive portion 22A is in contact with the base particle 2. Therefore, the first conductive portion 22A is disposed on the surface of the base particle 2, and the second conductive portion 22B is disposed on the outer surface of the first conductive portion 22A. The second conductive portion 22B is not in contact with the base particle 2. The conductive particle 21 has a plurality of protrusions 21a on the conductive surface. The conductive portion 22 has a plurality of protrusions 22a on the outer surface. The first conductive portion 22A has a protrusion 22Aa on the outer surface. The second conductive portion 22B has a plurality of protrusions 22Ba on the outer surface. In the conductive particle 21, the conductive portion 22 is a two-layer conductive portion (conductive layer). The conductive particle may have a third conductive portion disposed on the outer surface of the second conductive portion. The conductive portion may be a conductive portion having three or more layers.
[0081] Other details of the conductive particles will be described below. In the following description, "(meth)acrylic" means either or both of "acrylic" and "methacrylic", and "(meth)acrylate" means either or both of "acrylate" and "methacrylate".
[0082] [Base material particles] The base particles include resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles, and metal particles. The base particles may be core-shell particles having a core and a shell disposed on the surface of the core. The core may be an organic core. The shell may be an inorganic shell. Among them, base particles other than metal particles are preferred, and resin particles, inorganic particles other than metal particles, or organic-inorganic hybrid particles are more preferred. Resin particles or organic-inorganic hybrid particles are particularly preferred because they provide better effects of the present invention.
[0083] The base particles are preferably resin particles formed by resin. When the conductive particles are used to connect the electrodes, the conductive particles are placed between the electrodes, and then compressed by pressure bonding. If the base particles are resin particles, the conductive particles are easily deformed during the pressure bonding, and the contact area between the conductive particles and the electrodes is increased. This increases the reliability of the conduction between the electrodes.
[0084] As the resin for forming the above-mentioned resin particles, various organic substances are suitably used.As the resin for forming the above-mentioned resin particles, for example, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, polybutadiene, etc.; acrylic resins such as polymethyl methacrylate and polymethyl acrylate, etc.; polyalkylene terephthalate, polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, and the polymer obtained by polymerizing one or more of various polymerizable monomers having ethylenic unsaturated groups, etc. Since the hardness of the base particle can be easily controlled within a suitable range, it is preferable that the resin for forming the resin particles is a polymer obtained by polymerizing one or more polymerizable monomers having multiple ethylenically unsaturated groups.
[0085] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.
[0086] Examples of the non-crosslinkable monomer include styrene-based monomers such as styrene and α-methylstyrene; carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, and the like. p) Oxygen-containing (meth)acrylates such as acrylate, polyoxyethylene (meth)acrylate, glycidyl (meth)acrylate, etc.; nitrile-containing monomers such as (meth)acrylonitrile, etc.; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, etc.; acid vinyl esters such as vinyl acetate, vinyl butyrate, vinyl laurate, vinyl stearate, etc.; unsaturated hydrocarbons such as ethylene, propylene, isoprene, butadiene, etc.; and halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, chlorostyrene, etc.
[0087] Examples of the crosslinkable monomer include tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly ) Polyfunctional (meth)acrylates such as propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, etc.; silane-containing monomers such as triallyl (iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, vinyltrimethoxysilane, etc.
[0088] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group by a known method, such as a method of suspension polymerization in the presence of a radical polymerization initiator, and a method of swelling and polymerizing a monomer together with a radical polymerization initiator using non-crosslinked seed particles.
[0089] When the base particle is an inorganic particle other than a metal particle or an organic-inorganic hybrid particle, examples of the inorganic material for forming the base particle include silica and carbon black. The inorganic material is preferably not a metal. The particle formed by the silica is not particularly limited, but examples thereof include particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form a crosslinked polymer particle, and then baking the particle as necessary. Examples of the organic-inorganic hybrid particle include organic-inorganic hybrid particles formed by a crosslinked alkoxysilyl polymer and an acrylic resin.
[0090] When the base particles are metal particles, examples of the metal particles include silver, copper, nickel, silicon, gold, titanium, etc. However, the base particles are preferably not metal particles, and are preferably not copper particles.
[0091] The particle diameter of the base particle is preferably 0.1 μm or more, more preferably 1.0 μm or more, even more preferably 1.5 μm or more, particularly preferably 2.0 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 300 μm or less, even more preferably 50 μm or less, even more preferably 30 μm or less, even more preferably 8.0 μm or less, particularly preferably 5.0 μm or less, and most preferably 4.0 μm or less. When the particle diameter of the base particle is above the lower limit, the contact area between the conductive particles and the electrodes is increased, so that the reliability of conduction between the electrodes is further increased, and the connection resistance between the electrodes connected via the conductive particles is further reduced. Furthermore, when the conductive part is formed on the surface of the base particle by electroless plating, aggregation is less likely to occur, and aggregated conductive particles are less likely to be formed. When the particle diameter of the base particle is below the upper limit, cracks in the conductive part are less likely to occur, the conductive particles are easily compressed sufficiently, the connection resistance between the electrodes is further reduced, and the gap between the electrodes is further reduced.
[0092] The particle size of the base particle refers to the diameter when the base particle is spherical, and refers to the maximum diameter when the base particle is not spherical.
[0093] The particle diameter of the base particle is particularly preferably 2 μm or more and 5 μm or less. When the particle diameter of the base particle is within the range of 2 to 5 μm, the distance between the electrodes becomes small and even if the thickness of the conductive part is increased, small conductive particles can be obtained.
[0094] Furthermore, it is particularly preferable that the particle diameter of the base particles is 1.0 μm or more and 4.0 μm or less. When the particle diameter of the base particles satisfies this range, cracks in the conductive portion are significantly less likely to occur, and the connection resistance is further effectively reduced.
[0095] [Conductive part] The metal for forming the conductive part is not particularly limited. Examples of the metal include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, ruthenium, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, and alloys thereof. Examples of the metal include tin-doped indium oxide (ITO) and solder. Among them, tin-containing alloys, nickel, palladium, copper, or gold are preferred, and nickel or palladium is preferred, since they can further reduce the connection resistance between electrodes.
[0096] From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, the conductive part preferably contains at least nickel, palladium, ruthenium, copper, tungsten, molybdenum, phosphorus, boron, gold, platinum, or tin, and more preferably contains at least nickel. The conductive part preferably contains at least nickel, palladium, copper, tungsten, molybdenum, phosphorus, boron, gold, platinum, or tin, and may contain at least nickel. From the viewpoint of further suppressing cracking of the conductive part and further enhancing acid resistance, the conductive part having the crystal structure preferably contains at least nickel, palladium, ruthenium, copper, tungsten, molybdenum, phosphorus, boron, gold, platinum, or tin, and more preferably contains at least nickel, and preferably contains at least nickel, palladium, copper, tungsten, molybdenum, phosphorus, boron, gold, platinum, or tin, and may contain at least nickel.
[0097] The conductive part may be formed of one layer, as in the conductive particles 1 and 11. The conductive part may be formed of multiple layers, as in the conductive particle 21. That is, the conductive part may have a laminated structure of two or more layers. When the conductive part is formed of multiple layers, the outermost layer is preferably a gold layer, a nickel layer, a palladium layer, a copper layer, or an alloy layer containing tin and silver, and more preferably a gold layer. When the outermost layer is one of these preferred conductive layers, the connection resistance between the electrodes is further reduced. In addition, when the outermost layer is a gold layer, the corrosion resistance is further increased.
[0098] The method of forming the conductive part on the surface of the base particle is not particularly limited.The method of forming the conductive part includes, for example, electroless plating, electroplating, physical vapor deposition, and coating the surface of the base particle with a metal powder or a paste containing a metal powder and a binder.Among them, the method of electroless plating is preferred because the conductive part is easily formed.The method of physical vapor deposition includes vacuum deposition, ion plating, ion sputtering, and the like.
[0099] The particle diameter of the conductive particles is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 520 μm or less, more preferably 500 μm or less, even more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 20 μm or less. When the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, when electrodes are connected using the conductive particles, the contact area between the conductive particles and the electrodes becomes sufficiently large, and when the conductive part is formed, the conductive particles are unlikely to be aggregated. In addition, the gap between the electrodes connected via the conductive particles does not become too large, and the conductive part is unlikely to peel off from the surface of the base particle. In addition, when the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, the conductive particles can be suitably used for the application of conductive materials.
[0100] The particle size of the conductive particles means the diameter when the conductive particles are spherical, and means the maximum diameter when the conductive particles are other than spherical.
[0101] The thickness of the conductive part (the thickness of the entire conductive part) is preferably 0.005 μm or more, more preferably 0.01 μm or more, and preferably 10 μm or less, more preferably 1 μm or less, even more preferably 0.5 μm or less, and particularly preferably 0.3 μm or less. When the conductive part is multi-layered, the thickness of the conductive part is the thickness of the entire conductive layer. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity is obtained, and the conductive particles do not become too hard, and the conductive particles are sufficiently deformed when connecting between electrodes.
[0102] When the conductive part is formed of a plurality of layers, the thickness of the outermost conductive layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, and preferably 0.5 μm or less, more preferably 0.1 μm or less. When the thickness of the outermost conductive layer is equal to or more than the lower limit and equal to or less than the upper limit, the coating with the outermost conductive layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes becomes even lower. In addition, when the outermost layer is a gold layer, the thinner the gold layer, the lower the cost.
[0103] The thickness of the conductive portion can be measured by observing a cross section of the conductive particle using, for example, a field emission scanning electron microscope (FE-SEM).
[0104] The obtained conductive particles are added to Kulzer's "Technovit 4000" so that the content is 30% by weight, and dispersed to prepare a resin for embedding conductive particles for inspection. A cross section of the conductive particles is cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the resin for embedding.
[0105] Then, it is preferable to use a field emission scanning electron microscope (FE-SEM) to set the image magnification to 50,000 times, randomly select 50 conductive particles, and observe the conductive portion of each conductive particle. It is preferable to measure the thickness of the conductive portion of the obtained conductive particles, and take the arithmetic average of the thicknesses to determine the thickness of the conductive portion.
[0106] From the viewpoint of effectively increasing the conductivity, the conductive particles preferably have a conductive part containing nickel. In 100% by weight of the conductive part containing nickel, the content of nickel is preferably 50% by weight or more, more preferably 65% by weight or more, even more preferably 70% by weight or more, even more preferably 75% by weight or more, even more preferably 80% by weight or more, particularly preferably 85% by weight or more, and most preferably 90% by weight or more. In 100% by weight of the conductive part containing nickel, the content of nickel is preferably 100% by weight (total amount) or less, and may be 99% by weight or less, or may be 95% by weight or less. When the content of nickel is equal to or more than the lower limit, the connection resistance between the electrodes is further reduced. In addition, when there is little oxide film on the surface of the electrode or conductive part, the higher the content of nickel, the lower the connection resistance between the electrodes tends to be.
[0107] The method for measuring the content of the metal contained in the conductive portion is not particularly limited and may use various known analytical methods. Examples of the measuring method include absorption spectrometry and spectral analysis. In the absorption spectrometry, a flame absorption spectrometer and an electric heating furnace absorption spectrometer may be used. Examples of the spectral analysis include plasma emission spectrometry and plasma ion source mass spectrometry.
[0108] When measuring the average content of metals contained in the conductive part, it is preferable to use an ICP optical emission spectrometer. Examples of commercially available ICP optical emission spectrometers include an ICP optical emission spectrometer manufactured by HORIBA.
[0109] The conductive portion may contain phosphorus or boron in addition to nickel. The conductive portion may contain a metal other than nickel. When the conductive portion contains a plurality of metals, the plurality of metals may be alloyed.
[0110] In 100% by weight of the conductive part containing nickel and phosphorus or boron, the content of phosphorus or boron is preferably 0.1% by weight or more, more preferably 1% by weight or more, and preferably 10% by weight or less, more preferably 5% by weight or less. When the content of phosphorus or boron is equal to or less than the above lower limit or the above upper limit, the resistance of the conductive part is further reduced, and the conductive part contributes to reducing the connection resistance.
[0111] [Core substance] The conductive particles preferably have protrusions on the conductive surface. The conductive particles preferably have protrusions on the outer surface of the conductive part. The number of protrusions is preferably multiple. An oxide film is often formed on the surface of the electrodes connected by the conductive particles. Furthermore, an oxide film is often formed on the surface of the conductive part of the conductive particles. By using the conductive particles having the protrusions, the conductive particles are placed between the electrodes and then pressed together, so that the oxide film is effectively removed by the protrusions. Therefore, the electrodes and the conductive particles can be more reliably contacted, and the connection resistance between the electrodes can be reduced. Furthermore, when the conductive particles have an insulating material on the surface, or when the conductive particles are dispersed in a binder resin and used as a conductive material, the resin between the conductive particles and the electrodes can be effectively removed by the protrusions of the conductive particles. Therefore, the reliability of the conduction between the electrodes is further increased.
[0112] The core material is embedded in the conductive portion, which facilitates forming a plurality of protrusions on the outer surface of the conductive portion, although it is not necessary to use a core material to form protrusions on the conductive surface of the conductive particle and on the surface of the conductive portion.
[0113] Methods for forming the above-mentioned protrusions include a method in which a core substance is attached to the surface of a base particle and then a conductive portion is formed by electroless plating, a method in which a conductive portion is formed on the surface of a base particle by electroless plating, a core substance is attached, and then a conductive portion is formed by electroless plating, and a method in which a core substance is added at an intermediate stage in forming a conductive portion on the surface of a base particle by electroless plating.
[0114] The core material may be a conductive material or a non-conductive material. The conductive material may be, for example, a conductive non-metal such as metal, metal oxide, graphite, or a conductive polymer. The conductive polymer may be polyacetylene. The non-conductive material may be silica, alumina, barium titanate, zirconia, or the like. Among them, metal is preferred because it can increase the conductivity and effectively reduce the connection resistance. The core material is preferably a metal particle. As the metal material of the core material, the metals listed as the materials of the conductive material may be appropriately used.
[0115] Specific examples of the core material include barium titanate (Mohs hardness 4.5), nickel (Mohs hardness 5), silica (silicon dioxide, Mohs hardness 6-7), titanium oxide (Mohs hardness 7), zirconia (Mohs hardness 8-9), alumina (Mohs hardness 9), tungsten carbide (Mohs hardness 9), and diamond (Mohs hardness 10). The inorganic particles are preferably nickel, silica, titanium oxide, zirconia, alumina, tungsten carbide, or diamond, more preferably silica, titanium oxide, zirconia, alumina, tungsten carbide, or diamond, even more preferably titanium oxide, zirconia, alumina, tungsten carbide, or diamond, and particularly preferably zirconia, alumina, tungsten carbide, or diamond. The Mohs hardness of the core material is preferably 5 or more, more preferably 6 or more, even more preferably 7 or more, and particularly preferably 7.5 or more.
[0116] The shape of the core material is not particularly limited. The core material is preferably in the form of a lump. Examples of the core material include a particulate lump, an aggregate of a plurality of microparticles, and an amorphous lump.
[0117] The average diameter (average particle diameter) of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 0.9 μm or less, more preferably 0.2 μm or less. When the average diameter of the core material is not less than the lower limit and not more than the upper limit, the connection resistance between the electrodes is effectively reduced.
[0118] The "average diameter (average particle diameter)" of the core material refers to the number average diameter (number average particle diameter). The average diameter of the core material is determined by observing 50 random core materials under an electron microscope or optical microscope and calculating the average value.
[0119] The number of the protrusions per conductive particle is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle diameter of the conductive particle, etc.
[0120] The average height of the plurality of protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 0.9 μm or less, more preferably 0.2 μm or less. When the average height of the protrusions is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes is effectively reduced.
[0121] [Insulating material] The conductive particles preferably have an insulating material disposed on the surface of the conductive portion. In this case, when the conductive particles are used for connecting the electrodes, short-circuiting between adjacent electrodes can be further prevented. Specifically, when a plurality of conductive particles contact each other, an insulating material exists between the plurality of electrodes, so that short-circuiting between adjacent electrodes in the horizontal direction, rather than between upper and lower electrodes, can be prevented. In addition, when connecting the electrodes, the conductive particles are pressed by the two electrodes, so that the insulating material between the conductive portion of the conductive particles and the electrodes can be easily removed. When the conductive particles have a plurality of protrusions on the outer surface of the conductive portion, the insulating material between the conductive portion of the conductive particles and the electrodes can be more easily removed.
[0122] The insulating material is preferably insulating particles, since this allows the insulating material to be removed more easily when the electrodes are pressed together.
[0123] Specific examples of the insulating resin that is the material of the insulating substance include polyolefins, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked thermoplastic resins, thermosetting resins, and water-soluble resins.
[0124] The average diameter (average particle diameter) of the insulating material can be appropriately selected depending on the particle diameter of the conductive particles and the use of the conductive particles. The average diameter (average particle diameter) of the insulating material is preferably 0.005 μm or more, more preferably 0.01 μm or more, and preferably 1 μm or less, more preferably 0.5 μm or less. If the average diameter of the insulating material is above the lower limit, when the conductive particles are dispersed in the binder resin, the conductive parts of the multiple conductive particles are unlikely to contact each other. If the average diameter of the insulating particles is below the upper limit, there is no need to apply too much pressure or heat to a high temperature in order to remove the insulating material between the electrodes and the conductive particles when connecting the electrodes.
[0125] The "average diameter (average particle diameter)" of the insulating material refers to the number average diameter (number average particle diameter). The average diameter of the insulating material can be determined using a particle size distribution measuring device or the like.
[0126] (Method of manufacturing conductive particles) The method for producing a conductive particle according to the present invention includes a step of annealing a base particle and a conductive particle (pre-annealed conductive particle) having a conductive portion disposed on the surface of the base particle at 200° C. or higher. In the method for producing a conductive particle according to the present invention, the annealing process produces conductive particles in which the conductive portion does not contain hydrogen atoms or contains hydrogen atoms at 80 μg / g or less. In particular, it is preferable that the conductive portion having the crystal structure has been annealed.
[0127] In order to reduce the content of hydrogen atoms in the conductive portion, the annealing temperature is preferably 200°C or higher, more preferably 300°C or higher. The annealing temperature is lower than the thermal decomposition temperature of the base particle and lower than the thermal decomposition temperature of the conductive portion. The annealing temperature is preferably 30°C or lower than the thermal decomposition temperature of the base particle. The annealing temperature is preferably 800°C or lower, more preferably 500°C or lower.
[0128] In order to reduce the content of hydrogen atoms in the conductive portion, the annealing time is preferably 0.5 hours or more, more preferably 1 hour or more, and even more preferably 3 hours or more.
[0129] In order to reduce the content of hydrogen atoms in the conductive portion, the annealing treatment is preferably performed under a high-pressure atmosphere. The degree of vacuum during the annealing treatment is preferably 10 kPa or more, more preferably 50 kPa or more, and even more preferably 100 kPa or more.
[0130] In order to reduce the content of hydrogen atoms in the conductive portion, when annealing is performed under an atmospheric pressure atmosphere, it is preferable to perform the annealing in an inert gas atmosphere such as nitrogen or argon.
[0131] In order to form a uniform conductive portion, the conductive portion is preferably formed by electroless plating, and is preferably an electroless plated layer.
[0132] When the conductive part is formed by electroless plating, a high concentration of reducing agent is required because the plating surface area of the conductive particles is large, and therefore, a large amount of reducing agent is oxidized and decomposed to generate hydrogen, resulting in a relatively large amount of hydrogen atoms being contained in the conductive part.
[0133] Examples of methods for controlling the hydrogen content in the conductive portion include a method of minimizing the reducing agent concentration when forming the conductive portion by electroless nickel plating, a method of controlling the pH of the nickel plating solution, a method of controlling the temperature of the nickel plating solution, a method of adjusting the particle stirring speed of the nickel plating solution, a method of controlling the surface tension of particles in the nickel plating solution, and a method of adjusting the nickel concentration in the nickel plating solution.
[0134] The hydrogen content in the conductive portion can be controlled by adjusting the reducing agent concentration to a minimum level. A phosphorus-containing reducing agent is preferably used as the reducing agent. In addition, a boron-containing reducing agent can be used as the reducing agent to form a conductive layer containing boron.
[0135] The phosphorus-containing reducing agent may be sodium hypophosphite, etc. The boron-containing reducing agent may be dimethylamine borane, sodium borohydride, potassium borohydride, etc.
[0136] The content of hydrogen atoms in the conductive portion can be reduced by using a nickel plating solution in which the above-mentioned reducing agent has been adjusted to a concentration of 100 g / L or less and slowly dripping the solution at a rate of 100 ml / min or less into a suspension in which resin particles are dispersed.
[0137] As a method for controlling the hydrogen content in the conductive part, there is a method for controlling the pH of the nickel plating solution. When the pH of the nickel plating solution exceeds 8.0, the self-decomposition reaction of the reducing agent is frequent, so that the amount of hydrogen generated increases, and the hydrogen atom content in the conductive part increases. Therefore, in order to reduce the hydrogen atom content in the conductive part, the pH of the nickel plating solution is set to 8.0 or less, and the self-decomposition reaction of the reducing agent that does not contribute to nickel plating deposition is suppressed, thereby reducing the hydrogen atom content in the conductive part.
[0138] As a method for controlling the hydrogen content in the conductive part, there is a method for controlling the reaction temperature of the nickel plating solution. When the reaction temperature of the nickel plating solution exceeds 70°C, the self-decomposition reaction of the reducing agent is frequent, so that the amount of hydrogen generated increases, and the hydrogen atom content in the conductive part increases. Therefore, in order to reduce the hydrogen atom content in the conductive part, the reaction temperature of the nickel plating solution is set to 70°C or less, and the self-decomposition reaction of the reducing agent that does not contribute to nickel plating deposition is suppressed, thereby reducing the hydrogen atom content in the conductive part.
[0139] (Conductive materials) The conductive material according to the present invention includes the conductive particles and a binder resin. The conductive particles are preferably dispersed in the binder resin and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive particles and the conductive material are preferably used for electrical connection between electrodes. The conductive material is preferably a circuit connection material.
[0140] The binder resin is not particularly limited. Generally, an insulating resin is used as the binder resin. Examples of the binder resin include vinyl resin, thermoplastic resin, curable resin, thermoplastic block copolymer, and elastomer. The binder resin may be used alone or in combination of two or more.
[0141] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.
[0142] The conductive material and the binder resin preferably contain a thermoplastic component or a thermosetting component. The conductive material and the binder resin may contain a thermoplastic component or may contain a thermosetting component. The conductive material and the binder resin preferably contain a thermosetting component. The thermosetting component preferably contains a curable compound that can be cured by heating and a thermosetting agent. The thermosetting agent is preferably a thermal cationic curing initiator. The curable compound that can be cured by heating and the thermosetting agent are used in an appropriate compounding ratio so that the binder resin is cured. If the binder resin contains a thermal cationic curing initiator, acid is likely to be contained in the cured product. However, by using the conductive particles according to the present invention, the connection resistance between the electrodes can be maintained low.
[0143] In addition to the conductive particles and the binder resin, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.
[0144] The conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0145] In 100% by weight of the conductive material, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder resin is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged between the electrodes, and the electrical conductivity reliability of the connection target members connected by the conductive material is further increased.
[0146] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the reliability of conduction between the electrodes is further increased.
[0147] (Connection structure) A connection structure can be obtained by connecting the connection target members using the conductive particles or a conductive material containing the conductive particles and a binder resin. It is preferable that the connection part is formed of the conductive particles described above or a conductive material containing the conductive particles and a binder resin described above.
[0148] The above connection structure is preferably a connection structure comprising a first connection target member, a second connection target member, and a connection part connecting the first and second connection target members, and the material of the connection part is the above-mentioned conductive particles, or a conductive material containing the above-mentioned conductive particles and a binder resin. The above connection part is preferably a connection structure formed of the conductive particles of the present invention, or a conductive material containing the conductive particles and a binder resin. When conductive particles are used, the connection part itself is a conductive particle. That is, the first and second connection target members are connected by the conductive particles.
[0149] FIG. 4 is a schematic front cross-sectional view showing a connection structure using conductive particles according to a first embodiment of the present invention.
[0150] A connection structure 51 shown in Fig. 4 includes a first connection target member 52, a second connection target member 53, and a connection portion 54 connecting the first and second connection target members 52, 53. The connection portion 54 is formed by hardening a conductive material containing conductive particles 1. Note that in Fig. 4, the conductive particles 1 are shown in a simplified diagram for convenience of illustration. Instead of the conductive particles 1, conductive particles 11, 21, etc. may be used.
[0151] The first connection target member 52 has a plurality of first electrodes 52a on its surface (upper surface). The second connection target member 53 has a plurality of second electrodes 53a on its surface (lower surface). The first electrodes 52a and the second electrodes 53a are electrically connected by one or more conductive particles 1. Therefore, the first and second connection target members 52 and 53 are electrically connected by the conductive particles 1.
[0152] The method for producing the connection structure is not particularly limited. One example of the method for producing the connection structure is a method in which the conductive material is placed between the first connection target member and the second connection target member to obtain a laminate, and then the laminate is heated and pressurized. The pressure of the pressurization is 9.8×10 4 ~4.9×10 6 The heating temperature is about 120 to 220°C.
[0153] Specific examples of the connection target member include electronic components such as semiconductor chips, capacitors, and diodes, as well as electronic components such as printed circuit boards, flexible printed circuit boards, glass epoxy boards, and glass boards. The connection target member is preferably an electronic component. The conductive particles are preferably used for electrically connecting electrodes in electronic components.
[0154] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, silver electrodes, SUS electrodes, molybdenum electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.
[0155] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0156] Example 1 (1) Preparation of conductive particles Divinylbenzene copolymer resin particles (base particle A, "Micropearl SP-203" manufactured by Sekisui Chemical Co., Ltd.) with a particle diameter of 3.0 μm were prepared. 10 parts by weight of the above resin particles were dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and the solution was filtered to extract the resin particles. Next, the resin particles were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surfaces of the resin particles. The resin particles with the activated surfaces were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed to obtain a suspension (A).
[0157] Next, 1 g of nickel particle slurry (average particle diameter 150 nm) was added to the suspension (A) over a period of 3 minutes to obtain base particles with a core material attached thereto. In addition, 3 L of a nickel plating solution (pH 5.0) containing 50 g / L of nickel sulfate, 50 g / L of sodium hypophosphite, and 20 g / L of sodium citrate was prepared.
[0158] While stirring the obtained suspension (A) at 45°C, the nickel plating solution was dropped into the suspension (A) at 50ml / min to perform electroless nickel plating to form a nickel-phosphorus conductive layer, and then the plating solution was filtered to remove particles, which were washed with water and dried to obtain conductive particles. In this way, conductive particles having a conductive portion (thickness 102nm) formed on the surface of the base particle A were obtained.
[0159] Next, the conductive particles having the conductive portion formed on the surface of the base particle A were subjected to annealing treatment at a temperature of 300°C for 4 hours (annealing treatment conditions) under an atmospheric pressure of 100 KPa to obtain conductive particles. These conductive particles were used to prepare an anisotropic conductive paste.
[0160] (2) Preparation of anisotropic conductive paste An anisotropic conductive paste was obtained by blending 20 parts by weight of an epoxy compound (EP-3300P manufactured by Nagase ChemteX Corporation), 15 parts by weight of an epoxy compound (EPICLON HP-4032D manufactured by DIC Corporation) which is a thermosetting compound, and 5 parts by weight of a thermal cation generator (SAN-AID SI-60 manufactured by Sanshin Chemical Industry Co., Ltd.) which is a thermosetting agent, and then adding the obtained conductive particles so that the content in 100% by weight of the blend was 10% by weight. The mixture was then stirred at 2000 rpm for 5 minutes using a planetary mixer, to obtain an anisotropic conductive paste.
[0161] (3) Preparation of connection structure A A glass substrate was prepared having an Al-Ti4% electrode pattern (Al-Ti4% electrode thickness 1 μm) with an L / S of 20 μm / 20 μm on the top surface, and a semiconductor chip was prepared having a gold electrode pattern (gold electrode thickness 20 μm) with an L / S of 20 μm / 20 μm on the bottom surface.
[0162] The anisotropic conductive paste immediately after preparation was applied to the upper surface of the glass substrate to a thickness of 20 μm to form an anisotropic conductive material layer. Next, the semiconductor chip was laminated on the upper surface of the anisotropic conductive material layer so that the electrodes faced each other. Thereafter, a pressure heating head was placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the anisotropic conductive material layer was 170° C., and a pressure of 150 MPa was applied to harden the anisotropic conductive material layer at 180° C., thereby obtaining a connection structure A.
[0163] (4) Preparation of connection structure B A pressure and heat head was placed on the upper surface of the semiconductor chip, and a pressure of 100 MPa was applied to harden the anisotropic conductive material layer at 100°C. In the same manner as in connection structure A, a connection structure B was obtained.
[0164] Example 2 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that the nickel particle slurry (average particle diameter 150 nm) was changed to an alumina particle slurry (average particle diameter 150 nm).
[0165] Example 3 3 L of a nickel plating solution (pH 5.0) containing 50 g / L of nickel sulfate, 50 g / L of sodium hypophosphite, and 20 g / L of sodium citrate was prepared.
[0166] 0.5 L of a plating solution (pH 10.0) for forming protrusions containing 300 g / L of sodium hypophosphite was prepared.
[0167] While stirring the suspension (A) obtained in Example 1 at 45°C, the above nickel plating solution was added dropwise to the suspension (A) at 25 ml / min to perform electroless nickel plating and form a nickel-phosphorus conductive layer, after which the plating solution for forming protrusions was added dropwise at 5 ml / min to form protrusions. During the dropping of the plating solution for forming protrusions, the generated Ni protrusion nuclei were dispersed by ultrasonic stirring while nickel plating was performed.
[0168] Next, the above nickel plating solution was dropped at 25 ml / min to carry out electroless nickel plating, thereby forming a nickel-phosphorus conductive layer on the surface of the base particle A.
[0169] The plating solution was filtered to extract the particles, which were then washed with water and dried to obtain conductive particles. In this manner, conductive particles having a conductive portion (thickness 102 nm) formed on the surface of the base particle A were obtained.
[0170] Anisotropic conductive paste and connection structures A and B were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0171] Example 4 3 L of a nickel plating solution (pH 5.0) containing 50 g / L of nickel sulfate, 50 g / L of sodium hypophosphite, and 20 g / L of sodium citrate was prepared.
[0172] 0.5 L of a plating solution (pH 10.0) for forming protrusions containing 300 g / L of sodium hypophosphite was prepared.
[0173] A gold plating solution (pH 9.0) containing 10 g / L potassium gold cyanide, 20 g / L sodium citrate, 10 g / L ethylenediaminetetraacetic acid, and 15 g / L sodium hydroxide was prepared.
[0174] While stirring the suspension (A) obtained in Example 1 at 45°C, the above nickel plating solution was added dropwise to the suspension (A) at 20 ml / min to perform electroless nickel plating and form a nickel-phosphorus conductive layer, after which the plating solution for forming protrusions was added dropwise at 5 ml / min to form protrusions. During the dropping of the plating solution for forming protrusions, the generated Ni protrusion nuclei were dispersed by ultrasonic stirring while nickel plating was performed.
[0175] Next, the above nickel plating solution was dropped at 20 ml / min to carry out electroless nickel plating, thereby forming a nickel-phosphorus conductive layer on the surface of the base particle A.
[0176] The suspension was then filtered to extract the particles, which were then washed with water to obtain particles having a nickel-phosphorus conductive layer formed thereon. The particles were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed therein to obtain suspension (B).
[0177] Thereafter, while stirring the suspension (B) obtained above at 55° C., the gold plating solution was gradually added dropwise to the dispersed suspension (B) to perform gold plating. The gold plating solution was added dropwise at a rate of 2 mL / min to perform gold plating.
[0178] The suspension was filtered to take out the particles, which were then washed with water and dried to obtain conductive particles.
[0179] In this manner, conductive particles were obtained in which conductive portions (thickness 108 nm) plated with nickel-phosphorus and gold were formed on the surfaces of the base particles A.
[0180] Anisotropic conductive paste and connection structures A and B were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0181] Example 5 3 L of a nickel plating solution (pH 5.0) containing 50 g / L of nickel sulfate, 50 g / L of sodium hypophosphite, and 20 g / L of sodium citrate was prepared.
[0182] 0.5 L of a plating solution (pH 10.0) for forming protrusions containing 300 g / L of sodium hypophosphite was prepared.
[0183] A palladium plating solution (pH 7.0) containing 5 g / L of palladium chloride, 20 g / L of sodium formate, 5 g / L of ethylenediamine, and 20 g / L of DL-malic acid was prepared.
[0184] A gold plating solution (pH 9.0) containing 7 g / L potassium gold cyanide, 15 g / L sodium citrate, 7 g / L ethylenediaminetetraacetic acid, and 12 g / L sodium hydroxide was prepared.
[0185] While stirring the suspension (A) obtained in Example 1 at 45°C, the above nickel plating solution was added dropwise to the suspension (A) at 15 ml / min to perform electroless nickel plating and form a nickel-phosphorus conductive layer, after which the plating solution for forming protrusions was added dropwise at 5 ml / min to form protrusions. During the dropping of the plating solution for forming protrusions, the generated Ni protrusion nuclei were dispersed by ultrasonic stirring while nickel plating was performed.
[0186] Next, the above nickel plating solution was dropped at 15 ml / min to carry out electroless nickel plating, thereby forming a nickel-phosphorus conductive layer on the surface of the base particle A.
[0187] The suspension was then filtered to extract the particles, which were then washed with water to obtain particles having a nickel-phosphorus conductive layer formed thereon. The particles were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed therein to obtain suspension (B).
[0188] Thereafter, while stirring the suspension (B) obtained above at 50° C., the palladium plating solution was gradually added dropwise to the dispersed suspension (B) to perform palladium plating. The palladium plating solution was added dropwise at a rate of 5 mL / min to perform palladium plating.
[0189] Next, the suspension was filtered to extract the particles, which were then washed with water to obtain particles having nickel-phosphorus and palladium conductive layers formed thereon. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain suspension (C).
[0190] Thereafter, while stirring the suspension (C) obtained above at 55° C., the gold plating solution was gradually added dropwise to the dispersed suspension (C) to perform gold plating. The gold plating solution was added dropwise at a rate of 2 mL / min to perform gold plating.
[0191] The suspension was filtered to take out the particles, which were then washed with water and dried to obtain conductive particles.
[0192] In this manner, conductive particles were obtained in which conductive portions (thickness 106 nm) plated with nickel-phosphorus, palladium and gold were formed on the surfaces of the base particles A.
[0193] Anisotropic conductive paste and connection structures A and B were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0194] Example 6 3 L of a nickel plating solution (pH 6.0) containing 50 g / L of nickel sulfate, 20 g / L of dimethylamine borane, and 30 g / L of sodium citrate was prepared.
[0195] 0.5 L of a plating solution (pH 10.0) for forming protrusions containing 120 g / L of dimethylamine borane was prepared.
[0196] A palladium plating solution (pH 7.0) containing 5 g / L of palladium chloride, 20 g / L of sodium formate, 5 g / L of ethylenediamine, and 20 g / L of DL-malic acid was prepared.
[0197] A gold plating solution (pH 9.0) containing 7 g / L potassium gold cyanide, 15 g / L sodium citrate, 7 g / L ethylenediaminetetraacetic acid, and 12 g / L sodium hydroxide was prepared.
[0198] While stirring the suspension (A) obtained in Example 1 at 45°C, the above nickel plating solution was added dropwise to the suspension at 15 ml / min to perform electroless nickel plating and form a nickel-boron conductive layer, after which the plating solution for forming protrusions was added dropwise at 5 ml / min to form protrusions. During the dropping of the plating solution for forming protrusions, the generated Ni protrusion nuclei were dispersed by ultrasonic stirring while nickel plating was performed.
[0199] Next, the above nickel plating solution was dropped at 15 ml / min to carry out electroless nickel plating, thereby forming a nickel-boron conductive layer on the surface of the base particle.
[0200] The suspension was then filtered to extract the particles, which were then washed with water to obtain particles having a nickel-boron conductive layer formed thereon. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain suspension (B).
[0201] Thereafter, while stirring the suspension (B) obtained above at 50° C., the palladium plating solution was gradually added dropwise to the dispersed suspension (B) to perform palladium plating. The palladium plating solution was added dropwise at a rate of 5 mL / min to perform palladium plating.
[0202] Next, the suspension was filtered to extract the particles, which were then washed with water to obtain particles having nickel-phosphorus and palladium conductive layers formed thereon. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain suspension (C).
[0203] Thereafter, while stirring the suspension (C) obtained above at 55° C., the gold plating solution was gradually added dropwise to the dispersed suspension (C) to perform gold plating. The gold plating solution was added dropwise at a rate of 2 mL / min to perform gold plating.
[0204] The suspension was filtered to take out the particles, which were then washed with water and dried to obtain conductive particles.
[0205] In this manner, conductive particles were obtained in which conductive portions (thickness 106 nm) plated with nickel-boron, palladium and gold were formed on the surfaces of the base particles A.
[0206] Anisotropic conductive paste and connection structures A and B were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0207] Example 7 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that the annealing treatment conditions were changed so that conductive particles having a conductive portion formed on the surface of base particle A were annealed at a temperature of 300°C for 4 hours under an atmospheric pressure of 10 KPa.
[0208] Example 8 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that the annealing conditions were changed so that conductive particles having a conductive portion formed on the surface of base particle A were annealed at a temperature of 200°C for 4 hours under an atmospheric pressure of 100 KPa.
[0209] Example 9 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that base particle A was changed to base particle B, which differed from base particle A only in particle diameter, having a particle diameter of 2.5 μm.
[0210] Example 10 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that base particle A was changed to base particle C, which differed from base particle A only in particle diameter, having a particle diameter of 3.5 μm.
[0211] Example 11 The surface of divinylbenzene copolymer resin particles ("Micropearl SP-2025" manufactured by Sekisui Chemical Co., Ltd.) having a particle diameter of 2.5 μm was covered with an inorganic shell (thickness 250 nm) by a condensation reaction through a sol-gel reaction to obtain core-shell type organic-inorganic hybrid particles (base particle D).
[0212] Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that base particle A was changed to base particle D, and the annealing treatment conditions were changed so that conductive particles having a conductive portion formed on the surface of base particle D were annealed at a temperature of 400°C for 4 hours under an atmospheric pressure of 100 KPa.
[0213] Example 12 300 g of 0.13 wt % aqueous ammonia solution was placed in a 500 mL reaction vessel equipped with a stirrer and a thermometer. Next, a mixture of 4.1 g of methyltrimethoxysilane, 19.2 g of vinyltrimethoxysilane, and 0.7 g of silicone alkoxy oligomer ("X-41-1053" manufactured by Shin-Etsu Chemical Co., Ltd.) was slowly added to the aqueous ammonia solution in the reaction vessel. After hydrolysis and condensation reactions were allowed to proceed with stirring, 2.4 mL of 25 wt % aqueous ammonia solution was added, and the particles were isolated from the aqueous ammonia solution and the obtained particles were subjected to a 1000 sintering process under an oxygen partial pressure of 1000 sintering. -17 The mixture was then calcined at 350° C. for 2 hours at 250° C. atm to obtain organic-inorganic hybrid particles (base particles E) having a particle diameter of 3.0 μm.
[0214] Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that base particle A was changed to base particle E, and the annealing treatment conditions were changed so that conductive particles having a conductive portion formed on the surface of base particle E were annealed at a temperature of 500°C for 4 hours under an atmospheric pressure of 100 KPa.
[0215] Example 13 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 5, except that base particle A was changed to base particle F, which differed from base particle A only in particle diameter and had a particle diameter of 5.0 μm.
[0216] Example 14 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 5, except that base particle A was changed to base particle G, which differed from base particle A only in particle diameter and had a particle diameter of 10.0 μm.
[0217] Example 15 In a 1000 mL separable flask equipped with a four-neck separable cover, stirring blade, three-way cock, cooling tube and temperature probe, a monomer composition containing 100 mmol of methyl methacrylate, 1 mmol of N,N,N-trimethyl-N-2-methacryloyloxyethyl ammonium chloride and 1 mmol of 2,2'-azobis(2-amidinopropane) dihydrochloride was weighed into ion-exchanged water so that the solid content was 5% by weight, and then the mixture was stirred at 200 rpm and polymerized for 24 hours at 70°C under a nitrogen atmosphere. After the reaction was completed, the mixture was freeze-dried to obtain insulating particles having ammonium groups on the surface, an average particle size of 220 nm and a CV value of 10%.
[0218] The insulating particles were dispersed in ion-exchanged water under ultrasonic irradiation to obtain a 10 wt % aqueous dispersion of the insulating particles.
[0219] 10 g of the conductive particles obtained in Example 1 were dispersed in 500 mL of ion-exchanged water, 4 g of the aqueous dispersion of insulating particles was added, and the mixture was stirred at room temperature for 6 hours. After filtering through a 3 μm mesh filter, the mixture was washed with methanol and dried to obtain conductive particles with insulating particles attached thereto.
[0220] Observation with a scanning electron microscope (SEM) revealed that only one coating layer of insulating particles was formed on the surface of the conductive particles. Image analysis was used to calculate the coverage area of the insulating particles (i.e., the projected area of the particle diameter of the insulating particles) relative to an area of 2.5 μm from the center of the conductive particles, and the coverage rate was found to be 30%.
[0221] Comparative Example 1 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that the conductive particles having a conductive portion formed on the surface of the base particle A were not annealed.
[0222] Comparative Example 2 Conductive particles, anisotropic conductive paste, and connection structures A and B were obtained in the same manner as in Example 1, except that the annealing conditions were changed so that the conductive particles having a conductive portion formed on the surface of the base particle A were annealed in a nitrogen atmosphere at a temperature of 280°C for 2 hours.
[0223] (evaluation) (1) Hydrogen atom content in the conductive part The conductive portion (metal film) sample to be measured was collected as follows.
[0224] The conductive particles were pulverized using a ball mill with zirconia balls, and the conductive portion was completely peeled off from the base particle. The sample in which the conductive portion and the base particle were completely peeled off was separated into the conductive portion and the base particle using a sieve, and only the conductive portion was collected.
[0225] A temperature programmed desorption hydrogen analyzer ("PDHA-1000" manufactured by FIS Corporation) was used to measure the content of hydrogen atoms. The conductive part was heated in the temperature programmed desorption apparatus, and the trace amount of hydrogen generated was measured with a sensor gas chromatograph. Under a constant pressure of 3 GPa, the evacuated conductive part was gradually heated from 50°C to 400°C at a rate of 5°C / min. The released hydrogen atoms were measured with a detector.
[0226] The hydrogen atom content in the conductive portion was defined as the total amount of hydrogen atoms released from 50°C to 400°C.
[0227] (2) Crystallite size in cross-sectional observation of the conductive parts (first, second, and third conductive parts) The obtained conductive particles were added to Kulzer's "Technovit 4000" so that the content was 30% by weight, and dispersed to prepare a resin for embedding conductive particles for inspection. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the resin for embedding.
[0228] Using FE-SEM-EBSP (TSL), crystal grain mapping measurements were performed on the cross section of the conductive part of the conductive particle. The crystallite size was determined by checking the particle size distribution chart of the crystallite size. The crystallite size was calculated from the average value of the crystallite size (1) in the first conductive part, the crystallite size (2) in the second conductive part, and the crystallite size (3) in the third conductive part.
[0229] (3) Crystallite size based on the average crystallite size of each orientation Powder X-ray diffraction measurements were performed using an X-ray diffractometer (Rigaku Corporation, "RINT2500VHF"). The crystallite size was calculated from the half-width of the diffraction peak obtained by X-ray diffraction using CuKα radiation and the average crystallite size of the (111), (200), (220), (311), and (222) planes calculated from the Scherrer equation.
[0230] The XRD measurement conditions were 45 kV, 50 mA, a scan rate of 4.0 deg / min, a scan step of 0.02 deg, and a measurement range of 2θ from 5.0 deg to 110.0 deg.
[0231] The crystallite size was calculated by the following Scherrer formula.
[0232] D=Kλ / βcosθ D: Crystallite size K: Scherrer constant λ: wavelength of X-rays β: Half-width [rad] θ: Diffraction angle
[0233] (4) Crystallite size of conductive part measured by XRD Powder X-ray diffraction measurements were performed using an X-ray diffractometer (Rigaku Denki Co., Ltd., "RINT2500VHF"). The crystallite size was calculated from the half-width of the diffraction peak obtained by X-ray diffraction using CuKα radiation and the Williamson-Hall equation.
[0234] The XRD measurement conditions were 45 kV, 50 mA, a scan rate of 4.0 deg / min, a scan step of 0.02 deg, and a measurement range of 2θ from 5.0 deg to 110.0 deg.
[0235] The crystallite size was calculated by the following Williamson-Hall equation.
[0236] Δ2θ·cosθ / λ=0.9 / D+2ε·sinθ / λ D: Crystallite size λ: wavelength of X-rays Δ2θ: Half-width [rad] θ: Diffraction angle ε: Lattice strain
[0237] The crystallite size was calculated by plotting the above Williamson-Hall equation with 2sinθ / λ on the horizontal axis and Δ2θ·cosθ / λ on the vertical axis, and the crystallite size was calculated from the intercept of the straight line on the plot.
[0238] (5) Compressive elastic modulus when the conductive particles are compressed by 10% (10% K value) The compressive elastic modulus (10% K value) of the obtained conductive particles was measured by the method described above using a microcompression tester (Fisherscope H-100 manufactured by Fischer).
[0239] (6) Cracks in conductive parts The semiconductor chip was peeled off from the obtained connection structures A and B, and the peeled surface was observed. Whether or not cracks occurred in the conductive portion was evaluated for 50 conductive particles. The cracks in the conductive portion were evaluated according to the following criteria.
[0240] [Criteria for determining cracks in conductive parts] ○○○: The percentage of conductive particles with cracks in the conductive portion out of 50 conductive particles is 0 or more and less than 10 ○○: Out of 50 conductive particles, the percentage of conductive particles with cracks in the conductive portion is 10 or more and less than 20 ○: The ratio of conductive particles with cracks in the conductive portion out of 50 conductive particles is 20 or more and less than 30 △: Out of 50 conductive particles, the ratio of conductive particles with cracks in the conductive portion is 30 or more and less than 40 ×: The ratio of the number of conductive particles having cracks in the conductive portion out of 50 conductive particles is 40 or more
[0241] (7) Initial connection resistance X Connection resistance measurement: The connection resistance X between the opposing electrodes of the obtained connection structures A and B was measured by a four-terminal method. The initial connection resistance X was also evaluated according to the following criteria.
[0242] [Evaluation criteria for initial connection resistance X] ○○○: Connection resistance X is 2.0Ω or less ○○: Connection resistance X is greater than 2.0Ω and less than 3.0Ω ○: Connection resistance X is greater than 3.0Ω and less than 5.0Ω △: Connection resistance X is greater than 5.0Ω and less than 10Ω ×: Connection resistance X exceeds 10 Ω
[0243] (8) Connection resistance Y after exposure to acid conditions (long-term reliability) The obtained connection structures A and B were left for 100 hours in a high-temperature, high-humidity chamber at 85°C and a humidity of 85%. By leaving the connection structures A and B under the above conditions, the connection parts between the electrodes in the connection structures A and B were exposed to the presence of acid for a certain period of time due to a reaction between the water that had penetrated into the binder resin and the acid contained in the binder resin. After leaving the connection structures A and B, the connection resistance Y between the opposing electrodes of the connection structures was measured by a four-terminal method. In addition, the connection resistance Y after exposure to the presence of acid was evaluated according to the following criteria.
[0244] [Evaluation criteria for connection resistance Y after exposure to acid conditions] ○○○: Connection resistance Y is less than 1 time of connection resistance X ○○: Connection resistance Y is 1 time or more and less than 1.5 times the connection resistance X ○: Connection resistance Y is 1.5 times or more and less than 2 times the connection resistance X. △: Connection resistance Y is 2 times or more but less than 5 times the connection resistance X. ×: Connection resistance Y is 5 times or more than connection resistance X
[0245] The results are shown in Table 1 below.
[0246] [Table 1] [Explanation of symbols]
[0247] 1...Conductive particles 2...Base material particles 3...Conductive part 11...Conductive particles 11a...Protrusion 12...Conductive part 12a...Protrusion 13…core substance 14...Insulating materials 21...Conductive particles 21a...Protrusion 22...Conductive part 22a...protrusion 22A…First conductive part 22Aa…Protrusion 22B...Second conductive part 22Ba...Protrusion 51...Connection structure 52...First connection target member 52a...first electrode 53...Second connecting member 53a...second electrode 54…Connection
Claims
1. A conductive particle including a base particle (excluding copper particles as the base particle) and a conductive portion (excluding a solder layer as the conductive portion) disposed on a surface of the base particle, The conductive particles have a particle diameter of 50 μm or less, The conductive portion contains at least nickel, palladium, or gold, The conductive particles are conductive particles (1) that do not have a core material embedded in the conductive portion, or conductive particles (2) that have a core material embedded in the conductive portion, In the case of the conductive particle (1), the conductive portion does not contain hydrogen atoms or contains hydrogen atoms in an amount of 80 μg / g or less, In the case of the conductive particle (2), the combined substance of the conductive portion and the core material contains hydrogen atoms at 3.6 μg / g or more and 65.2 μg / g or less (however, the conductive particle (2) does not include conductive particles in which the conductive portion contains hydrogen atoms in excess of 80 μg / g).
2. The conductive particle (1) according to claim 1.
3. The conductive particle (2) according to claim 1.
4. the conductive portion includes a conductive portion having a crystalline structure, The conductive particle according to any one of claims 1 to 3, wherein, in cross-sectional observation of the conductive portion having a crystalline structure, the crystallite size in the conductive portion having a crystalline structure is 50 nm or more.
5. the conductive portion includes a conductive portion having a crystalline structure, The conductive particle according to any one of claims 1 to 4, wherein in the conductive portion having a crystalline structure, the crystallite size calculated from the average value of the crystallite sizes of the (111) plane, the (200) plane, the (220) plane, the (311) plane and the (222) plane calculated from the half-width of the diffraction peak obtained by X-ray diffraction and the Scherrer formula is 50 nm or more.
6. the conductive portion includes a conductive portion having a crystalline structure, The conductive particle according to any one of claims 1 to 5, wherein in the conductive portion having a crystalline structure, a crystallite size calculated from a half-width of a diffraction peak obtained by X-ray diffraction and the Williamson-Hall equation is 50 nm or more.
7. The compressive elastic modulus when compressed by 10% is 3000 N / mm 2 The conductive particle according to any one of claims 1 to 6, wherein
8. The conductive particle according to any one of claims 1 to 7, wherein the conductive portion has a Vickers hardness of 200 or more.
9. The conductive particle according to any one of claims 1 to 8, wherein the conductive portion contains at least nickel.
10. The conductive particle according to any one of claims 1 to 9, wherein the base particle is a resin particle or an organic-inorganic hybrid particle.
11. The conductive particle according to any one of claims 1 to 10, comprising an insulating material disposed on an outer surface of the conductive portion.
12. A method for producing conductive particles according to claim 1, comprising the steps of: The method includes a step of annealing the conductive particles at 200° C. or higher using conductive particles having a base particle (excluding copper particles as the base particle) and a conductive portion (excluding a solder layer as the conductive portion) disposed on a surface of the base particle, The conductive particles (1) or (2) are obtained by the annealing treatment.
13. A conductive material comprising the conductive particles according to any one of claims 1 to 11 and a binder resin.
14. A first connection target member; A second connection target member; a connection portion that connects the first connection target member and the second connection target member, A connection structure, wherein a material of the connection portion is the conductive particle according to any one of claims 1 to 11, or a conductive material containing the conductive particle and a binder resin.
Citation Information
Patent Citations
Conductive paste
JP1998106351A
Manufacture of solder plated cu ball
JP1998200245A
Solder plating method for spherule
JP1998270836A
Method for manufacturing solder-coated ball
JP2005133178A
Conductive particle, conductive material, and connection structure
JP2013149613A